PENGARUH DEBT TO EQUITY RATIO DAN NET PROFIT MARGIN TERHADAP PERATAAN LABA DENGAN ROA SEBAGAI VARIABEL MODERASI (Studi Kasus Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Periode 2011-2015) - Elok Kurniawati (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2019)
This research aims to know the influence of debt to equity ratio and net profit margin toward income smoothing and the influence of roa as the moderate correlation. The object for this research is mining company listed on the Indonesia Stock Exchange (BEI) in the period 2011-2015. This study uses Eckel Index to classify a company that does or does not practice income smoothing. The sample used in this study is a 10 mining companies listed on the Stock Exchange in the five years from 2011 to 2015 with the selection purposive sampling method. The statistical analysis used in this study with descriptive statistics and multiple linear regression. The result of this research shows that either simultaneously or partially, the variable of net profit margin influence negatively with the income smoothing on the Indonesia Stock Exchange (BEI). But variable debt to equity ratio do not influence the income smoothing.